HUBUNGAN LETAK LESI HEMISFER SEREBRAL DAN DERAJAT KLINIS KECEMASAN PADA PENDERITA STROKE ISKEMIK - Yelly Marliana Patu; Audry Devisanty Wuysang; Nadra Maricar (NEURONA, 2018)
RELATIONSHIP BETWEEN LOCATION OF CEREBRAL HEMISPHERE LESION AND CLINICAL DEGREES OF ANXIETY IN ISCHEMIC STROKE PATIENTSABSTRACTIntroduction: Stroke is the leading cause of disability and the third cause of death in the world. The lesion in the right hemisphere is most often associated with anxiety.Aim: Knowing the relationship between the location of the lesion and the degree of anxiety in patients with acute ischemic post-stroke.Method: Cross-sectional study of 40 ischemic post-stroke patients at Wahidin Sudirohusodo Hospital and network- ing hospitals in January-April 2018.  The degree of anxiety was measured by the Hamilton Anxiety Rating Scale (HARS). Chi-square and Mann-Whitney tests were used to analyze the relationship between variables with a p value <0.05 consid- ered significant.Result: There was a significant relationship between the location of the lesion in the hemisphere and the HARS score (p=0.01); and between the location of infarction lesions (cortical and subcortical) with the degree of anxiety in patients with ischemic stroke (p=0.012).Discussion: Moderate-severe anxiety levels occur higher in the lesions in the right hemisphere. The clinical instru- ments used cannot eliminate the element of subjectivity.Keywords: Anxiety in stroke, ischemic stroke, left hemisphere, lesion location, right hemisphereABSTRAKPendahuluan: Stroke merupakan penyebab utama kecacatan dan kematian ketiga terbanyak di dunia. Lokasi lesi di hemisfer kanan merupakan lokasi lesi yang paling sering dikaitkan dengan timbulnya kecemasan.Tujuan: Mengetahui hubungan antara lokasi lesi dan derajat kecemasan pada penderita pascastroke iskemik akut.Metode: Desain potong lintang pada 40 sampel penderita pascastroke iskemik di RS Wahidin Sudirohusodo dan rumah sakit jejaring pada bulan Januari-April 2018. Derajat kecemasan diukur dengan Hamilton Anxiety Rating Scale (HARS). Uji Chi-square dan Mann-Whitney digunakan untuk menganalisis hubungan antar variabel dengan nilai p<0,05 dianggap bermakna.Hasil: Terdapat hubungan yang signifikan antara lokasi lesi di hemisfer dengan skor HARS (p=0,01); dan antara lokasi lesi infark (kortikal dan subkortikal) dengan derajat kecemasan pada penderita stroke iskemik (p=0,012).Diskusi: Derajat kecemasan sedang-berat lebih tinggi terjadi pada lesi di hemisfer kanan.  Instrumen klinis yang digunakan tidak dapat menghilangkan unsur subjektifitas.Kata kunci: Cemas pada stroke, hemisfer kanan, hemisfer kiri, letak lesi, stroke iskemik